EXPERIMENTAL MODEL OF SINGLE-PHASE DC–DC BOOST CONVERTER FOR 1000 WP PHOTOVOLTAIC APPLICATION - Handoko Rusiana Iskandar; Muhammad Rizky Alfarizi; Ajie Prasetya; Nana Heryana (SINERGI, 2021)
The photovoltaic system is used and utilized as electricity demand in many developed countries, including Indonesia. Nowadays, the photovoltaic system is an alternative source of inexpensive, reasonably priced electricity and easily applied in public facilities until laboratory usage. In Electrical Engineering Laboratory (EEL), Faculty of Engineering (FoE), Universitas Jenderal Achmad Yani is 1 kWp peak photovoltaic application available. The PV system is planned to be connected to the grid and produces 220VAC / 50Hz characteristics to meet the existing load capacity. The PV systems modeled include Pulse Width Modulation (PWM) controlled DC/DC Boost Converter, and DC/AC converter circuit. This study's experimental architecture is proposed to meet the electrical load following the characteristics of the photovoltaic device. The three types of electronic switching control, namely Metal Oxide Semiconductor Field Effect Transistor (MOSFET), Insulated Gate Bipolar Transistor (IGBT) and Gate Turn-off Thyristor (GTO), are used to achieve the highest performance. Based on the 1 kWp photovoltaic system's simulation results from the three types of electronic power switching, a minimum output voltage range of 210-230 VDC is produced. DC/AC Converter testing has been carried out and can be tested on a grid-connected 220VAC/50Hz single phase with the highest output using MOSFET equal to 96.7%.